Combined ditch buried straw return technology in a ridge–furrow plastic film mulch system: Implications for crop yield and soil organic matter dynamics - Li, Yüze; Song, Duanpu; Dang, Pengfei; Wei, Lina; Qin, Xiaoliang; Siddique, Kadambot H.M. (Soil & tillage research, 2020)
•A ridge–furrow plastic film mulch (RP) configuration with ditch buried straw return:•Is a sustainable practice in rainfed agricultural areas.•Increased soil organic carbon concentrations more than flat cultivation and RP without buried straw.•Increased total nitrogen in surface soil, relative to the other two treatments.•Increased maize yield more than the other two treatments. A ridge–furrow plastic film mulch (RP) configuration can increase crop and straw yields in semiarid areas of China. This study advocated for a novel soil tillage practice (ditch buried straw return) in a ridge–furrow plastic film mulch system. There were three treatments: (i) flat cultivation, CK; (ii) ridge–furrow plastic film mulch with no straw return (RP−S); and (iii) ridge–furrow plastic film mulch with ditch buried straw return (RP+S). Field experiments were conducted from 2015 to 2018 on the Loess Plateau of China to study the effects of straw incorporation on maize growth, biomass, water use efficiency, soil organic carbon, and total nitrogen sequestration capacity in RP systems. The mean rate of straw decomposition in RP+S reached 81 % at harvest of each year. The RP systems provided suitable hydrothermal conditions for maize growth. Both RP treatments promoted maize growth, particularly biomass accumulation and plant height under RP+S. The RP+S treatment also had greater concentrations of soil organic carbon and total nitrogen in surface soil at harvest, higher total nitrogen accumulation, nitrogen content and crude protein in maize grain, and higher maize yields and water use efficiencies than the other two treatments. In summary, the introduction of ditch buried straw return to RP is an effective measure for promoting the sustainable development of film mulching systems in semiarid regions of China by improving soil fertility and increasing crop yields.